Depresión asociada a la disfunción familiar en los estudiantes de octavo y noveno año de educación básica sección matutina del Colegio Adolfo Valarezo de la ciudad de Loja. En el periodo junio-noviembre de 2014 - Procel Barragán, Margoth de los Ángeles (2015)
This study is a quantitative type, descriptive and analytic cross whose purpose was to determine the relationship between family functioning and depression in a sample of 288 students between the ages of 11-15 years male and female attending the eighth and ninth year of Basic Education "Adolfo Valarezo" College. Family APGAR was used to assess family functioning and Beck test to determine the degree of depression data were processed through Excel 2010 program which were processed and analyzed with descriptive statistics. It was determined that 18.75% of students who participated in this study present relationship between depression and family dysfunction, the 39.93% have good family function while 60.07% have family dysfunction predominantly mild family dysfunction. According to depression by classification test Beck 72.57% no depression while 27.43% had depression, distributed 18.75% with mild depression, 5.90% moderate depression, 1.39% severe depression and extreme depression 1, 39%. Keywords : family dysfunction , depression, adolescence.